ANALISIS PERAN BADAN USAHA MILIK DESA (BUMDes) DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) DESA DI KOTA AMBON - Wattiheluw, Nur ‘Ain Unsari; Loupatty, Linda Grace (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the role of Village-Owned Enterprises (BUMDes) in achieving the Village Sustainable Development Goals (SDGs) in Ambon City, with a focus on four main pillars: social development, economisdevelopment, environmental sustainability, and legal and governance systems. The research employs a descriptive qualitative approach, with data collocted through in-depth interviews, observation, and documentation of five BUMDes across five districts in Ambon City: Nusaniwe District (BUMDes Gideon Nusaniwe Sakti), Sirimau District (BUMDes Rurehe), Leitimur Selatan District (BUMDes Rajunohitipori), Teluk Ambon Baguala District (BUMDes Waipipi), and Teluk Ambon District (BUMDes Waisarot). The findings reveal that BUMDes play a vital role and have a positive impact on the realization of the four SDGs pillars. BUMDes contribute to poverty reduction by creating job opportunities, promote local economis growth through microenterprise development, initiate environmental conservation programs, and strengthen transparency and accountability in village governance. However, several challenges remain, including limited capital, low managerial capacity, and lack of innovation. Therefore, greater support from the government, private sector, and academia is needed to enchance the effectiveness of BUMDes in achieving sustainable village development goals. Keyword: bumdes, village sdgs, social development pillar, economic development pillar, environmental development pillar, legal and governance pillar